Apolipoprotein M promotes cholesterol uptake and efflux from mouse macrophages. Issue 6 (2nd May 2021) - Yao, Shuang; Zheng, Fan; Yu, Yang; Zhan, Yuxia; Xu, Ning; Luo, Guanghua; Zheng, Lu
Abstract : Apolipoprotein M (ApoM) exhibits various anti‐atherosclerotic functions as a component of high‐density lipoprotein (HDL) particles. Scavenger receptor class B type I (SR‐BI) is a classic HDL receptor that mediates selective cholesterol uptake and enhances the efflux of cellular cholesterol to HDL. However, the effect of ApoM on cholesterol transport in macrophages remains unclear. In this study, we identified for the first time that ApoM is expressed in mouse macrophages and is involved in cholesterol uptake, similar to SR‐BI. NBD‐cholesterol uptake and efflux in cells were characterized using fluorescence spectrophotometry. The uptake ratios of cholesterol by macrophages from ApoM −/− SR‐BI −/− mice were significantly lower than those from ApoM +/+ SR‐BI −/− and ApoM −/− SR‐BI +/+ mice. Real‐time fluorescence quantitative PCR was used to analyze the expression of cholesterol transport‐related genes involved in cholesterol uptake. ApoM‐enriched HDL (ApoM + HDL) facilitated more cholesterol efflux from murine macrophage Ana‐1 cells than ApoM‐free HDL (ApoM − HDL). However, recombinant human ApoM protein inhibited the ability of ApoM − HDL to induce cholesterol efflux. In conclusion, ApoM promotes cholesterol uptake and efflux in mouse macrophages. A better understanding of ApoM function may lead to the development of novel therapeutic strategies for treating atherosclerotic diseases. Abstract : In this study, we mainly explore the role of ApoM in two aspects: the uptake and efflux of cholesterol in mouse macrophages. ApoM deficiency leads to decreased cholesterol uptake by mouse peritoneal macrophages. ApoM + HDL promotes cellular cholesterol efflux more efficiently than ApoM − HDL does. It is quite possible that ApoM promotes cholesterol efflux by SR‐BI‐dependent mechanisms.